2022
DOI: 10.3390/su14020670
|View full text |Cite
|
Sign up to set email alerts
|

The Agro-Waste Production in Selected EUSAIR Regions and Its Potential Use for Building Applications: A Review

Abstract: The purpose of this study is to provide a snapshot of the agro-waste production in Puglia, Molise, Albania and Montenegro, some of the regions belonging to EUSAIR (ADRIATIC-IONIAN REGIONS) correlating this aspect to the possible use of agro-waste in the building sector. EUSAIR is a functional area, facing the Adriatic sea, treating the marine, coastal and terrestrial areas as interconnected systems. In the first part of the paper, the state of the art about the current consumption of agricultural biomass is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A study identified coconut and rice husks as one of the main AWBs used to produce biopolymers for construction applications [20]. In line with the findings of other studies, it is evident that fibrous AWBs such as rice husks, cereal straw and bagasse are suitable for thermal and acoustic insulation applications [21,37,65].…”
Section: Main Types and Properties Of Awbs Used By Categorymentioning
confidence: 69%
See 1 more Smart Citation
“…A study identified coconut and rice husks as one of the main AWBs used to produce biopolymers for construction applications [20]. In line with the findings of other studies, it is evident that fibrous AWBs such as rice husks, cereal straw and bagasse are suitable for thermal and acoustic insulation applications [21,37,65].…”
Section: Main Types and Properties Of Awbs Used By Categorymentioning
confidence: 69%
“…Examples include activated binders, insulation products, alternative cementitious materials in concrete, bricks, and reinforced concrete panels [5,. Other studies have analysed the feasibility of its use in specific regions [31,37]. However, the authors are not aware of extensive and comprehensive research on the use of AWB in the construction industry.…”
mentioning
confidence: 99%
“…Nevertheless, the issue of agro-waste burning is linked to environmental pollution and is restricted in several countries or provinces [248]. Agro-waste can be dealt innovatively through composting, producing bioactive compounds, nanomaterials, and biorefinery tools [249].…”
Section: Type Of Biosensors Function Materials Type Referencementioning
confidence: 99%
“…In recent years, natural lignocellulosic materials, such as hemp, bamboo, ax, sisal, etc., have become the most signi cant reinforcing materials in polymer matrices. The use of these wood-based raw materials involves cutting plant bres, contributing to the triple planetary crisis: loss of biodiversity, pollution, and climate change [6], [7]. With increasing areas of application of polymer composites, the consumption of wood-based raw materials is expected to increase.…”
Section: Introductionmentioning
confidence: 99%